Uma avaliação do instituto do negociado sobre o legislado e seus reflexos nas relações de trabalho. - Silva, Louânya Karol Ferreira da (2024)
The work seeks to analyze the institute of Prevalence of the Negotiated over the Legislated, a novelty introduced by article 611-A of the Consolidation of Labor Laws, from Law nº 13,467/2017. To this end, an exhibition was made of the historical advances in Labor Law, both at a global and national level, taking as a starting point the process of globalization and progress in the social field. Furthermore, the work carries out an empirical analysis that is based on interviews carried out by the author with formal and informal workers, as well as legal professionals. These interviews address the new institute that prioritizes what is negotiated over what is legislated, in addition to exploring the nuances of reform in contemporary labor relations. The analysis is complemented by the narrative of a legal case that reached the Federal Supreme Court, contributing to the formation of understanding on the topic. The analysis of the creation and evolution of labor rights is justified by the importance of understanding whether the new decision of the Federal Supreme Court (STF) represents an advance or a setback for workers' rights. In this sense, it is questioned whether the prevalence of a collective norm over current legislation could have been validated by the STF, the guardian body of constitutional rights, which is why it is necessary to determine whether this decision violated any constitutional norm. The objective of this study is to evaluate the institution of the Negotiated Legislation and its effects on labor relations, with special attention to the defense of the principle of worker protection, since the publication of the Labor Reform. The methodology adopted for this study involved documentary analysis and jurimetrics, using as a basis historical material that covers scientific articles, relevant legislation and the judicial process that culminated in the Federal Supreme Court (STF). Furthermore, the approach was descriptive in relation to the technical procedures used. Data were collected through guided interviews, using a script structured according to the "snowball" method. As a result of all these elements, even considering the STF's understanding, the proposed conclusion for the problem under debate is the need to implement actions that guide workers about their rights.